Factors Predicting Job Retention of Professional Nurses at Yala Hospital - ชัยกองเกียรติ, ปรียนุช (Princess of Naradhiwas University Journal, 2018)
This descriptive research aimed to examine job retention and factors predicting the job retention. The samples of this study were 248 professional nurses working at Yala Hospital. The participants were conducted through simple random sampling.. The research instrument utilized in this study was a questionnaire. Content validity index was verified by three experts: IOC, yielding values of 0.92.. The reliability was verified by using Cronbach’s alpha coefficient, yielding values of 0.95.. The data were analyzed using mean, standard deviation, Pearson product moment correlation coefficient and stepwise multiple regression analysis. The results of this study revealed that the personal factors related to a high level of job retention were the responsibilities to nurture of their families (M=4.11, S.D.=0.88), their hometown or houses located near by the hospital (M=4.07, S.D.=1.02). In addition, the organizational factors consisted of colleagues’ relationships (M=3.79, S.D.=0.72). The mean working duration of professional nurses working at Yala hospital was 10.13 years (S.D.=9.11). 73.4 percent thought they would like to continue their work until being retired. Moreover, age, hometown, perspectives, and income could predict the variance of the job retention of the nurses (87.3%). Therefore, these findings could be a significant guide for organizational administrators to set up policies and promote strategies to strengthen retention of quality professional nurses in order to meet effectivenursing services.